Genomic imprinting of Grb10: coadaptation or conflict? - Jon F Wilkins (PLoS Biology)
Mammalian development involves significant interactions between offspring and mother. But is this interaction a carefully coordinated effort by two individuals with a common goal--offspring survival? Or is it an evolutionary battleground (a central idea in our understanding of reproduction). The conflict between parents and offspring extends to an offspring's genes, where paternally inherited genes favor demanding more from the mother, while maternally inherited genes favor restraint. This "intragenomic conflict" (among genes within a genome) is the dominant evolutionary explanation for "genomic imprinting." But a new study in PLOS Biology provides support for a different perspective: that imprinting might facilitate coordination between mother and offspring. According to this "coadaptation theory," paternally inherited genes might be inactivated because maternally inherited genes are adapted to function harmoniously with the mother. As discussed in this article, the growth effects associated with the imprinted gene Grb10 are consistent with this idea, but it remains to be seen just how general the pattern is.